Deriving Mental Energy From Task Completion - Wang, Xiang; Janiszewski, Chris; Zheng, Yanmei; Laran, Juliano; Jang, Wonseok Eric (Frontiers in Psychology, 2021)
Many tasks in everyday life (e.g., making an accurate decision, completing job tasks, searching for product information) are extrinsically motivated (i.e., the task is performed to gain a benefit) and require mental effort. Prior research shows that the cognitive resources needed to perform an extrinsically motivated task are allocated pre-task. The pre-task allocation of mental resources tends to be conservative, because mental effort is costly. Consequently, there are mental energy deficits when the use of mental resources exceeds the allocated amount. This research provides evidence for post-task mental energy replenishment. The amount of resource replenishment is a function of the size of the mental energy deficit and the favorability of the cost-benefit trade-off experienced at the completion of the task (i.e., the value of the reward given the energy investment). The findings have implications for how cognitive resources management influences the availability of mental energy on a moment-to-moment basis.